Creative and knowledge economies and their linkages with other economic sectors: analysis for the Catalonia Region - Eduardo Chica; Carlos Marmolejo (European Regional Science Association (ERSA), 2011)
The increase in the last decades of the weight of the creative industries and knowledge-intensive sectors (KIS) in the economies of metropolitan areas is transforming the dynamics of urban development, for access of these sectors to agglomeration economies, such as skilled labor and good communication infrastructures. Polycentrism is helping in such a process. In this paper the interactions of the KIS with other economic sectors are analyzed in order to know the relationship between levels of economic dependence of economic sectors and their spatial patterns. In doing so, the input-output matrix of Catalonia, where is located the MRB, is analysed by means of multidimensional scaling techniques and compared to the geographical distance among sectors. Results suggest a little correlation between economic dependence and geographic distance from the different economic sectors, and a high correlation factor was found when considered in isolation of the KIS. This phenomenon could be the result of great economic dependence of all economic sectors to the KIS, which are located mostly in the center of all relations of the region's economy; consequently, KIS are localized geographically around the whole territory, although, more concentrated than others sectors.
Keywords: 330